Cover Image, Volume 60, Issue 4‐5. Issue 4 (14th May 2022) - Li, Xufeng; Zhang, Zhenqian; Han, Maoying; Li, Yang; He, Lingjuan; Zhou, Bin
Abstract : Cover illustration : Cover Image © Immunostaining for GFP (green, which represented the expression of Piezo1), E‐CAD (red) on intestine sections of 10‐week‐old Piezo1‐CreER; Rosa26‐Ai47 mice after tamoxifen treatment. genesis, e23476. https://doi.org/10.1002/dvg.23476